ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYISIHAN PENGHAPUSAN AKTIVA PRODUKTIF (PPAP) (Studi Komparasi Bank Konvensional & Bank Syariah di Indonesia) - Rinanti, Risna (JURNAL BISNIS STRATEGI, 2012)
Loan loss provisioning is an allowance that is established by charging current operations to accommodate the losses that may arise as a result of the receipt all or part of productive assets. Loan loss provisioning ratio indicates the ability of bank management in maintaining asset quality so that the amount of allowance for loan loss provisioning can be managed properly.The purpose of this study is to determine differences in the factors that affect the loan loss provisioning between conventional banks and Islamic banks. Variables that affect the loan loss provisioning is firm size (SIZE), capital adequacy ratio (CAR), loan-to-debt-to-ratio (LDR) and earnings before tax and provisionsÂ  (EBTP). Method of data collection was purposive sampling. The research data is secondary data Islamic banks and conventional banks for four consecutive years from 2008-2011. The statistical method used is multiple regression and chow test.These results indicate that firm size (SIZE), capital adequacy ratio (CAR), loan-to-debt-to-ratio (LDR) and earnings before tax and provisionsÂ  (EBTP) in conventional banks have a significant effect on the loan loss provisioning. While not a significant factor is firm size (SIZE), capital adequacy ratio (CAR), loan-to-debt-to-ratio (LDR) and earnings before tax and provisions (EBTP) in Islamic banks. Chow test results of the analysis indicate that there are differencesbetween the factors that influence the PPAP in conventional and Islamic banks is that the ratio of the size or the size of the company konvensinal bank has total assets greater than Islamicbanks. This reflects how much the total assets owned by describing the capital, as well as itsrights and obligations. Further analysis chow test on Islamic banking when seen from a comparison of the CAR indicates that the effect of the CAR to PPAP under conventional banking.